Peran Kaolin Clay dan Karbon Aktif dalam Produksi Gas Hidrogen dengan Metode Fotokatalisis - ; S, Sudarman (Fakultas Teknik UMSU, 2022)
The energy crisis is a challenge in the industrial sector. Hydrogen is environmentally friendly alternative energy. This study aims to determine the role of kaolin clay and activated carbon in hydrogen production by the photocatalysis method. Hydrogen production was carried out in a closed tube reactor with a total volume of 500 mL filled with 100 mL of pure water and the remainder for air. 300 W halogen lamp was used as the light energy source. The photocatalysis test temperature was maintained at 70oC. The hydrogen gas was measured using the MQ-8 sensor connected to the Arduino Uno atmega 328p microcontroller and a computer. From the results of photocatalysis testing, kaolin clay photocatalyst has a significant role in the production of hydrogen gas. The use of 10 mg of kaolin clay was able to produce hydrogen gas of 81 mol h-1. This value was the highest when compared to the use of an activated carbon photocatalyst or the combination of kaolin clay with activated carbon. Kaolin clay which has a content of 7.58% silica and a high electron density has an important function for the dissociation of hydrogen and covalent bonds in photocatalysis solutions.